Care Leavers' Experiences of Transition and Turning Points: Findings from a Biographical Narrative Study - John Pinkerton; Carmel Rooney (Social Work and Society, 2014)
This paper reports on the findings of a PhD research project that set out to explore how young people leaving out of home care experienced and made sense of their transition to adulthood. Using the Biographical Narrative Interpretative Method, in-depth accounts were collected and analysed for eight care leavers. The data suggest that in addition to care leavers living their lives as a series of biographical events, their 'care career', they also experience changes in the way they make sense of their lives which form a 'subjective pathway'. Influenced by the literature on resilience, the research had anticipated that 'turning point' events would play a significant role in the young people's subjective pathways. But the findings show a more gradual, phased shifting of subjectivity. It is suggested that legislation, policy, services and care practices need to facilitate this more drawn out 'subjective pathway'. Attachment, resilience and humanistic social psychology are proposed as useful theoretical underpinnings for that work.